Assessment of prescription pattern and impact of statin in lipid profile among ischemic heart disease patients - Sagar Kunnaruvath Prabhakaran; Kala Bahadur Rawal; Basavaraj Utagi; Uday Venkat Mateti; Shraddha Shetty (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Analysis of prescription patterns and lipid profiles can play a crucial role in rational drug use and patient safety. This study aimed to analyze the prescription pattern and impact of statin in lipid profile among ischemic heart disease (IHD) patients. MATERIALS AND METHODS: A prospective observational study was conducted for 7 months in the cardiology department. IHD patients above 18 years and undergoing statin therapy for at least 3 months were enrolled. Patients with elevated liver enzymes and unfit for statin therapy, pregnant women, psychiatry patients, and critically ill subjects were excluded. RESULTS: Of the total participants, 214 (71.8%) were males and 84 (28.2%) were females, with a mean age of 62.55 ± 9.56 years. The most common age group diagnosed with IHD was between 60 and 69 years. Hypertension was observed in 64.4% of the patients, while diabetes was present in 55.7% as the most commonly associated comorbidities. The majority of patients (75.8%) received atorvastatin. The prescription pattern for various drug classes included proton pump inhibitors (93%), antiplatelet agents (82.2%), statins (82.2%), nitrates (60.4%), beta-blockers (34.6%), diuretics (16.8%), biguanides (17.4%), and insulin (15.1%). After 3 months of statin therapy, a statistically significant change was observed in the lipid profile (P < 0.001). CONCLUSION: Statin agents were the most frequently prescribed class of drugs, followed by antiplatelets. Significant improvements were observed in the lipid profile after a 3-month course of statin therapy. Effective therapeutic monitoring can significantly impact a positive health outcome in patients.